If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 2 + 10x = -4 + 3x + 48 Reorder the terms: 2 + -1x + 10x = -4 + 3x + 48 Combine like terms: -1x + 10x = 9x 2 + 9x = -4 + 3x + 48 Reorder the terms: 2 + 9x = -4 + 48 + 3x Combine like terms: -4 + 48 = 44 2 + 9x = 44 + 3x Solving 2 + 9x = 44 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 9x + -3x = 44 + 3x + -3x Combine like terms: 9x + -3x = 6x 2 + 6x = 44 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 6x = 44 + 0 2 + 6x = 44 Add '-2' to each side of the equation. 2 + -2 + 6x = 44 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 44 + -2 6x = 44 + -2 Combine like terms: 44 + -2 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| x-35/8=(-2.5) | | 1/4=5/4x+2/3 | | 9x+3+x=2+5x+26 | | (z-5)/4 | | -.1(x+27)+.3(x+3)=x-17 | | -(7y+4)-(-6y-7)=-2 | | x^2+y^2-22y+121=121 | | .8x-.2x+4=.7x | | -(4x-10)+2(3x+5)=0 | | 4x/11+3/11=-1 | | x^2+y^2-22y=0 | | 77-32= | | 16(2x-8)=4(8x+3) | | 8+16m-7=9m+29-7m | | 8+6m-7=9m+29-7m | | 2z+7z=63 | | x^2-4x=13 | | 20t=56 | | 7/9x=532 | | 2.1q-3.8-2.9q=-1.8q-2.6 | | 4/7=(-3w+2)/-2w | | (7m-6)/6=16/12 | | 2k-k=.18 | | 3x^3-6x^2-4x-8=0 | | x^2-3x-0= | | 4n^6-28n^5-32n^4= | | 2b-25+5b=7-35 | | 16(8.5)+12(y)=160 | | 16(x)+12(2)=160 | | (4x-18)/2 | | 11x+5=9x+25 | | 11x-7=5x+7 |